Development of the Ophthalmohygienic Methods for the Vision Conditions Optimization and Protection of Organs of Vision of the Personnel during Ukrainian Antarctic Expeditions - V. G. Martirosova; Ye. V. Moiseyenko (Ukrainian Antarctic Journal, 2003)
Organs of vision status examination of the Ukrainian Antarctic expedition members was carried out. It was worked out and used the new optical techniques of unfavorable solar radiation protection under Antarctic conditions. Using of special colour filters will provide aggressive radiation protection of organs of vision and optimal vision conditions, promoting personnel efficiency and health preservation.